TATO DALAM KARYA LUKIS REALIS KONTEMPORER - AMIRAL HUSAINI, Yasrul Sami, S.Sn., M.Sn., Drs. Erfahmi, M.Sn. (Serupa The Journal of Art Education, 2017)
Human being creating as perfect creature, but human always want more form with changing them body form with tattoo, lately tattoo become life style and show strength power, so that’s why tattoo become badness symbol to freeman among society. Different the things of with society of dayak and Mentawai, tattoo represent religious symbol or nature balance. Making of this final masterpiece aim to visualizing tattoo in masterpiece paint contemporary realist, the result : Tangan Dibelenggu ( Bagian Satu), Tangan Dibelenggu ( Bagian Dua), Tangan Dipenjara, Dua Tangan Dibelenggu, Kaki Dibelenggu, Tangan Diborgol, Belenggu Tangan, Borgol Sementara (Bagian Satu), Borgol Sementara (Bagian Dua), Borgol jariKata Kunci : Tato, Karya Lukis Realis Kotemporer